Biodegradation of lignocellulosic agricultural residues by a newly isolated Fictibacillus sp. YS-26 improving carbon metabolic properties and functional diversity of the rhizosphere microbial community. (August 2020) - Chen, Yufeng; Wang, Wei; Zhou, Dengbo; Jing, Tao; Li, Kai; Zhao, Yankun; Tang, Wen; Qi, Dengfeng; Zhang, Miaoyi; Zang, Xiaoping; Luo, Yanping; Xie, Jianghui
Graphical abstract: Highlights: A cellulolytic bacterium Fictibacillus sp. was identified from a soft coral. Strain YS-26 degrades various agro-residues by producing different cellulases. Strain YS-26 enhances carboxylic acids and polymers metabolism capacity. Strain YS-26 improves the functional diversity of soil microbial community. Abstract: A new isolated cellulolytic bacterium from a soft coral was named as Fictibacillus sp YS-26 based on the morphologic and molecular characteristics. It can degrade different lignocellulosic agricultural residues by producing cellulolytic enzymes, α -amylase, protease, pectinase and xylanase. Especially, Fictibacillus sp. YS-26 exhibited the highest cellulolytic activities in the soybean meal medium. By contrast, the fermentation broth of Fictibacillus sp. YS-26 significantly enhanced utilization efficiency of carboxylic acids and polymers by soil microorganisms as well as the microbial metabolism function and community diversity in rhizosphere soil of banana plantlets. The fermentation broth also improved soil characters and increased the growth of banana plantlets. We found that soil total nitrogen and electrical conductivity had a positive relationship with the increase of microbial diversity. Hence, Fictibacillus sp. YS-26 will be a promising candidate for biodegradating lignocellulosic biomass and improving the soil microbial diversity.